A study of thyroid status in hyperemesis gravidarum - Gill, Bhupinder Kaur (Springer India, 2007)
Study was undertaken to assess thyroid status in hyperemesis gravidarum. 150 women pregnant with <20 weeks of gestation were selected randomly and out of these 100 women presenting with hyperemesis formed study group while 50 normal pregnant women served as controls. 53% of hyperemetic pregnant women were primigravidae and 82% of pregnant women presented with vomiting at less than 12 weeks of gestation. Statistically significant, 22% of hyperemetic women had increased serum T(3) levels while T(4) levels were increased in 67% of women in study group as compared to 8% and 16% respectively in control group. TSH levels were decreased in 18% of hyperemetic women as compared to 8% in control group with decrease in mean TSH level statistically significant. 22% of hyperemetic women had electrolyte disturbances and 7% were ketonuric. In clinically euthyroid women, biochemically altered thyroid function can attribute to vomiting and its prolongation to second trimester